Pengaruh Kompetensi Guru dan Strategi Pembelajaran Terhadap Mutu Pendidikan di MTs Negeri 2 Brebes - Baridin, Baridin (Kelompok Kajian Pendidikan Ikatan Alumni IAIN Purwokerto, 2018)
The aim of this research is to know the influence of teacher competence and learning strategy toward the quality of education in MTs Negeri 2 Brebes. School as a system should produce output whose capacity can be guaranteed. School output is generally measured from the level generated through the process of schooling. School performance is measured by its effectiveness, quality, productivity, efficiency, innovation, quality of work life, surplus and morale. This study examines three main variables: teacher competence, application of learning strategy and quality of education. The step of this research are defining the problem based on existing theories and the real condition, arranging instruments based on indicators, processing the data and analyzing it using statistical formulas. The results of this research are 1) there is significant influence of teacher competence to the quality of education, 2) there is significant influence of application of learning strategy to quality of education and 3) there is influence of teacher competence and implementation of learning strategy together to quality of education.